(untitled) (Research, Society and Development, 2022)
This research evaluated the cytoprotective effects of L-carnitine on the testis of albino rats treated with vincristine sulfate in the prepubertal stage. Ninety animals were used, 30 of which were controls, 30 treated with vincristine sulfate, and 30 treated with L-carnitine and vincristine sulfate. Drug applications occurred at 15 days of life, and euthanasia at 40, 64, and 127 days of life, allowing the analysis of the gonads at different stages of development. Biometric measurements (body weight, absolute testicular weight, relative testicular weight, testicular volume, major and minor testicular axes) and stereological measurements (length and volume densities of the seminiferous tubules and interstitial tissue) were performed. The results showed that the preventive use of L-carnitine can reduce the testicular deleterious effects caused by vincristine sulfate, since variables such as absolute testicular weight, relative testicular weight, and testicular minor axis indicated the mitigation of damages resulting from the action of the antineoplastic, mainly in acute and subacute phases.